Contribution of biogenic sources to secondary organic aerosol in the summertime in Shaanxi, China. (September 2020) - Xu, Yong; Chen, Yonggui; Gao, Jingsi; Zhu, Shengqiang; Ying, Qi; Hu, Jianlin; Wang, Peng; Feng, Liguo; Kang, Haibin; Wang, Dexiang
Abstract: A revised Community Multi-scale Air Quality (CMAQ) model with updated secondary organic aerosol (SOA) yields and a more detailed description of SOA formation from isoprene (ISOP) oxidation was applied to study the spatial distribution of SOA, its components and precursors in Shaanxi in July of 2013. The emissions of biogenic volatile organic compounds (BVOCs) were generated using the Model of Emissions of Gases and Aerosols from Nature (MEGAN), of which ISOP and monoterpene (MONO) were the top two, with 1.73 × 10 9  mol and 1.82 × 10 8  mol, respectively. The spatial distribution of BVOCs emission was significantly correlated with the vegetation coverage distribution. ISOP and its intermediate semi-volatile gases were up to ∼7.0 and ∼1.4 ppb respectively in the ambient. SOA was generally 2–6 μg/m 3, of which biogenic SOA (BSOA) accounted for as high as 84% on average. There were three main BVOCs Precursors including ISOP (58%) and MONO (8%) emit in the studied domain, and ISOP (9%) transported. The Guanzhong Plain had the highest BSOA concentrations of 3–5 μg/m 3, and the North Shaanxi had the lowest of 2–3 μg/m 3 . More than half of BSOA was due to reactive surface uptake of ISOP epoxide (0.2–0.7 μg/m 3, ∼19%), glyoxal (GLY) (0.2–0.5 μg/m 3, ∼11%) and methylglyoxal (MGLY) (0.4–1.4 μg/m 3, ∼32%), while the remaining was due to the traditional equilibrium partitioning of semi-volatile components (0.1–1.2 μg/m 3, ∼25%) and oligomerization (0.2–0.4 μg/m 3, ∼12%). Overall, SOA formed from ISOP contributed 1–3 μg/m 3 (∼80%) to BSOA. Graphical abstract: Image 1 Highlights: BVOCs concentration matched well with the vegetation coverage. Isoprene and its intermediate semi-volatile gases were the highest. BSOA accounted for 84% of SOA in Shaanxi, of which ISOP made up 67%. BSOA was unexpectedly high in Guanzhong.